Distinct Impacts of the Central and Eastern Atlantic Niño on the European Climate - Baiyang Chen; Lei Zhang; Chunzai Wang (Geophysical Research Letters)
Abstract The Atlantic Niño is the primary interannual variability mode in the tropical Atlantic, with far‐reaching impacts on global climate. A recent study identified two types of the Atlantic Niño, each with its maximum warming centered in the central and eastern equatorial Atlantic, respectively. Through analysis of observational data and numerical model experiments, we find that the two Atlantic Niño types have distinct climatic impacts on Europe. This is because the central Atlantic Niño is associated with a pronounced increase in precipitation in the western tropical Atlantic, while the positive precipitation anomalies during the eastern type are mainly located in the eastern basin with weaker amplitudes. Consequently, compared to the eastern Atlantic Niño, the extra‐tropical atmospheric waves and the associated precipitation and temperature anomalies in Europe during the central type are stronger and shifted westward. Therefore, distinguishing between the two Atlantic Niño types may help improve seasonal climate predictions in Europe.